Madrasah Teacher Performance Improvement Through Madrasah Head Leadership and Teacher Motivation - Imaduddin Imaduddin (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This study was conducted at Madrasah Schools using quantitative research methods under the supervision of the Sunan Giri Prigen Foundation. Respondents in the study were 63 people. Direct distribution of a questionnaire to the respondents served as the method of data collection. The respondents then employed statistics to analyze the information or responses. The tests for normality, linearity, heteroscedasticity, and multicollinearity are the ones that come next. Validity and dependability are also examined by these tests.. The evaluation of the multiple linear regression data analysis comes next, and the study hypothesis is checked in the last test. The study's conclusions show that every component of the research question has been accepted as true and reliable. The conventional assumption test's findings demonstrated that this study could use all of the data. The results showed that the leadership of the madrasa head had a favorable influence of 40.1%. The principal's leadership style and teacher competency both have a positive and considerable impact on kids' emotional intelligence, and there is a 33% effect of motivation on teacher performance.